From bondage to freedom : memories of the freedom struggle in Orissa - Nayak, Jatindra K.; Mohanti, Arun K. (Bhubaneswar : Rupantar, 2006)
Translated articles on history of Orissa from memories of 20th century nationalists from Orissa
Library has 2 copies
Includes bibliographical references
Keywords: Nationalists -- Orissa -- Biography; Orissa -- Biography; Orissa (India) -- History -- 20th century